PTU-062 Significant response to local ablative bridging treatments facilitates acceptable rates of survival following liver transplantation for HCC in a UK centre. (28th May 2012) - Lochan, R; Coates, R; French, J; reeves, H; Jaques, B; White, S; Manas, D
Abstract : Introduction: Liver Transplantation (LT) is a well-recognised treatment option for selected patients with hepatocellular carcinoma (HCC). However there is always concern regarding tumour progression while on the waiting list. As yet there is no agreed consensus on how to reduce progression of disease while waiting. UK guidelines recommend local ablative therapy for all HCC patients being considered for LT. We have sought to review this practice and evaluate its benefit. Methods: All consecutive patients with HCC who have undergone LT between 2001 and 2010 were identified from our prospectively maintained database. All patients are discussed at our LT assessment meeting and also at a separate HPB MDT for consideration of bridging treatment. Our imaging protocol includes (1) triple phase CT to assess the number of hyper vascular liver lesions, presence of venous washout, or extra-hepatic disease, (2) MRI to re-characterise any atypical lesions or (3) CEUS for further characterisation. Patients undergo either trans-arterial chemo-embolisation (TACE) and/or percutaneous/laparoscopic radio frequency ablation (RFA) while on the LT waiting list. The response to bridging treatment is assessed and intensive surveillance for disease progression is also undertaken. Results: 55 HCC patients underwent LT (M:F=43:12), Childs-Pugh A (n=9), B (n= 30) and C (n=16). Bridging treatments were either TACE n=31, RFA n=28, or both treatments n=4. TACE treatments per patient were 1 (n=12), 2 (n=12), 3 (n=6) or 4 (n=1). Six patients did not undergo any form of bridging treatment as they rapidly progressed to LT. The response to bridging treatment was complete (n=8), good (n=28), poor (n=4) or no response (n=15). There were two deaths within 100 post-operative days. At last follow-up, 28 patients had died due to recurrent disease, stable recurrent disease n=4 or disease free n= 21. Overall survival [median (95% CI)] was 62 (53–71) months. For those with a good response to bridging treatments it was 67 (55–79) months while for those with poor/no response it was 53 (42–64) months (log-rank p=0.059). Conclusion: This study demonstrates the feasibility of various bridging treatments for patients with HCC who await liver transplantation in the UK. In combination with careful patient selection and surveillance acceptable rates of survival can be achieved. Competing interests: None declared.